The Impact of Pre-analytical Quality Initiatives on Cholangiocarcinoma Diagnostics in Thailand - Koonmee, Supinda; Sangkhamanon, Sakkarn; Intarawichian, Piyapharom; Aphivatanasiri, Chaiwat; Kunprom, Waritta; Sa-ngiamwibool, Prakasit; Balthaisong, Suwit; Phuyao, Chitsakul; Prajumwongs, Piya; Alaghehbandan, Reza; Thanee, Malinee (Frontiers in Public Health, 2022)
Cholangiocarcinoma (CCA) is the most prevalent malignancy in Thailand, with unfortunate late diagnosis and frequent metastatic disease outcomes. An accurate tissue diagnosis is the first and most important step in the treatment of CCA. Tissue quality and preservation during the pre-analytical phase play major roles in the proper histological evaluation and potential biomarker testing. This study evaluated the impact of using the “Cholangiocarcinoma Screening and Care Program (CASCAP)” container, as an innovative tool to address pre-analytical challenges faced by pathology laboratories in Thailand. This is a comparison study examining the quality of CCA specimens using the CASCAP container vs. the conventional method, using hematoxylin and eosin (H&E) and immunohistochemistry (IHC). CCA tissue quality using the CASCAP container significantly reduced artifact deposition while improving the cellular structure and nuclear and cytoplasmic morphologies. The immunohistochemical expression of cytokeratin 19 (CK19), a prognostic marker in CCA, significantly improved in the CASCAP container group in comparison with the conventional method. This innovation is proven to significantly enhance the CCA tissue quality diagnostics and prognostic biomarker testing, hence improving overall cancer care, diagnosis, and treatment in Thailand.